1995
DOI: 10.1346/ccmn.1995.0430105
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Process of Phlogopite in Acid Solutions

Abstract: Abstract--The alteration experiments of phlogopite with 0.01 N HC1 solution containing 0.1 M NaC1 at 50*, 80* and 120"C have been carried out to aid in the understanding of the dissolution process of mica and the formation of secondary phases such as vermiculite and interstratified mica/vermiculite. Twenty milligrams of phlogopite samples were suspended in 20 ml or 100 ml of leaching solution.In these experiments, the dissolution ofphlogopite occurred incongruently, where the preferential release of K occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…Kuwahara and Aoki reported that phlogopite dissolved preferentially in the order of K > Mg ≈ Al > Si within 96 h in 0.01 M HCl þ 0.1 M NaCl solution at elevated temperature (323-393 K). 15 Another study of phlogopite in water at 1 atm CO 2 and room temperature reported that Mg dissolution was preferred over Si dissolution, 16 while the present work shows similar dissolution rates of Mg and Si. The different behavior of phlogopite at low CO 2 pressure (1 atm) or in acid solution, and under GCS conditions (this work), suggests that the reaction mechanisms between rock minerals and CO 2 -saturated saline water could differ from changes in ambient conditions.…”
Section: ' Results and Discussionsupporting
confidence: 52%
“…Kuwahara and Aoki reported that phlogopite dissolved preferentially in the order of K > Mg ≈ Al > Si within 96 h in 0.01 M HCl þ 0.1 M NaCl solution at elevated temperature (323-393 K). 15 Another study of phlogopite in water at 1 atm CO 2 and room temperature reported that Mg dissolution was preferred over Si dissolution, 16 while the present work shows similar dissolution rates of Mg and Si. The different behavior of phlogopite at low CO 2 pressure (1 atm) or in acid solution, and under GCS conditions (this work), suggests that the reaction mechanisms between rock minerals and CO 2 -saturated saline water could differ from changes in ambient conditions.…”
Section: ' Results and Discussionsupporting
confidence: 52%
“…This study for 1, 4, 10, and 56 day dissolution of biotite, respectively, 5 = this study for 5.5 day dissolution of phlogopite, 6 = Malmström and Banwart (1997), and 7 = Kuwahara and Aoki (1995). Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/1/15 6:47 PM sibly a kaolin polymorph) were also observed.…”
Section: Naturally Weathered Biotitementioning
confidence: 71%
“…Similar observations also have been made using lattice-imaging techniques (Reichenbach et al 1988;Veblen et al 1993;Aoudjit et al 1996;Dong et al 1998). Vermiculitization and/or kaolinitization are found for some biotite dissolution experiments (Kuwahara and Aoki 1995;Kalinowski and Schweda 1996;Malmström and Banwart 1997), but are not observed or reported for others Clemency and Lin 1981;Acker and Bricker 1992;Turpault and Trotignon 1994).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Kalinowski and Schweda (1996) found a continuous preferential leaching of interlayer K without any significant modification to the cationic composition of the 2:1 layer. Kuwahara and Aoki (1995) studied the dissolution of phlogopite in 0.01 N HCl/0.1 M NaCl solutions at pH 2 from 50 to 120°C. They observed nearly congruent dissolution at 50°and 80°C.…”
Section: Stoichiometry Of Dissolutionmentioning
confidence: 99%